2021
DOI: 10.2217/fvl-2021-0266
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence of Sofosbuvir/Velpatasvir as an Effective and Simple Hepatitis C Virus Treatment and Elimination Tool in Homeless Populations

Abstract: Background: People experiencing homelessness are disproportionately affected by hepatitis C virus (HCV) and can face specific barriers to care. Simple treatment algorithms could increase linkage to care in this population. Methods: This retrospective real-world analysis pooling data from 15 clinical cohorts evaluated effectiveness of a once-daily sofosbuvir/velpatasvir (SOF/VEL) regimen in HCV-infected people experiencing homelessness. The primary outcome was sustained virological response (SVR) in the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Individuals infected with HCV genotype 1-6, with or without compensated cirrhosis, who initiated treatment with a 12week SOF/VEL 400/100 mg regimen (without ribavirin) as part of routine clinical practice, were eligible for inclusion. The full study methodology is available in previously published retrospective analyses of the effectiveness of SOF/VEL in other special populations (homeless and prison populations) [26,27]. Patients were managed and treated according to local guidelines and standards of care.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals infected with HCV genotype 1-6, with or without compensated cirrhosis, who initiated treatment with a 12week SOF/VEL 400/100 mg regimen (without ribavirin) as part of routine clinical practice, were eligible for inclusion. The full study methodology is available in previously published retrospective analyses of the effectiveness of SOF/VEL in other special populations (homeless and prison populations) [26,27]. Patients were managed and treated according to local guidelines and standards of care.…”
Section: Methodsmentioning
confidence: 99%
“…For some treatment regimens, adherence was measured in clinical studies as completion of ≥80% of the treatment, while other studies have applied a threshold of ≥90%. [13][14][15][16] However, a real-world evidence (RWE) study showed that with DAA treatment, those who achieved at least 50% adherence had an overall SVR rate of 99%, demonstrating that suboptimal adherence to DAA treatment may still lead to HCV cure. [17] Different methods have been used to assess patients' adherence to treatment regimens, and this can affect reported adherence rates.…”
Section: Considerations In Evaluating Hcv Therapy Adherencementioning
confidence: 99%
“…A retrospective RWE study analyzed pooled data from 15 clinical cohorts of HCVinfected people experiencing homelessness treated with a once-daily SOF/VEL regimen. [14] Among 153 patients treated with SOF/VEL without ribavirin (RBV), SVR was 100% in the effectiveness population (EP; n = 122) irrespective of various baseline factors, such as active injection drug use and mental health disorders. Treatment adherence data were available for 98 of 122 patients (80.3%) in the EP.…”
Section: Accepted Manuscriptmentioning
confidence: 99%